Inequality in Latin America: The role of the nature of trade and partners - Teresa María García Mu\~noz; Juliette Milgram Baleix; Omar Odeh Odeh (Kiel Institute for the World Economy (IfW), 2019)
This paper investigates the relationship between trade openness and income inequality in 11 Latin American countries over the period 1989-2015. We use a panel dynamic approach to take into account the high persistence of income inequality. The analysis classifies trade flows, exports and imports according to trading partner's economic development and income level. Then, we split trade flows according to different stages of production. The results show that overall trade flows lessen income inequality in Latin America. However, trade has divergent effects depending on the trade partners: trade with similar-income countries exacerbates inequality, while trade with developing countries and higher-income countries reduces income dispersion. The results also emphasise the role of the export channel (in particular in primary commodities) in explaining income inequality in Latin American countries and imports of consumption goods seem to matter more than imports of intermediate and capital goods.
Keywords: F14; O54; E25; 330; trade openness; trade direction; income inequality; Latin America